Hydrographic properties of water masses in the Amazonas River plume obtained in April/May 2021 by CTD measurements during RV METEOR cruise M174 - Volker Mohrholz; Toralf Heene; Robert Mars; Jens Söder; Ajit Subramaniam (PANGAEA, 2022)
As result of population growth and human development, many low latitude river-ocean systems are undergoing fundamental changes. The RV METEOR cruise M174 (https://doi.org/10.1594/PANGAEA.935041) was dedicated to understanding the links between the Amazon River and the adjacent tropical ocean, which are critical components of any attempt to address the ecosystem extquotesingles health and productivity. This CTD dataset covers the Amazon River plume on the Brazilian shelf, the shelf of French Guinea and the adjacent offshore area as an example for such ecosystems. The data set has been obtained with a CTD SBE 911plus in April and May 2021, and contains vertical profiles of pressure, temperature, practical salinity, dissolved oxygen concentration, turbidity, and nitrate concentration.